PROSE OF MARKA CHEREMSHYN: LITERARY CLASSIC IN A METAMODERN PRISM - Matsevko-Bekerska, Lidia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
Marko Cheremshyna’s literary work was a vivid and original response to the demands of the historical and cultural discourse of his time. Modern literary criticism from the perspective of the post-apocalyptic interval cognizes the essence of the author’s style and inscribes it in the coordinates of each reader’s current experience of his or her own place in the historical and cultural chronotope. M. Cheremshyna’s prose provides rich material for cognizing its cognitive and narrative originality, for understanding the writer’s artistic style. Such a methodological perspective is all the more convincing because it opens up space for comprehending the "structure of feeling" (R. Williams) as one of the basic concepts of the modern metamodern paradigm. While for researchers of the Ukrainian writer’s style, his modernist content and the corresponding text design did not raise any objections or doubts, for a contemporary reader of the next century, it is quite logical to turn the "polaroid lens" towards the metamodern projections of M. Cheremshyna’s prose, especially in the perception/understanding/interpretation of a literary text. Similar to the modernist search for a holistic reflection of the world and its most subjective experience, the current era seeks to get rid of chaos and despondency, requiring clarity, intelligibility, mimetic display, harmony of perception, and integrity of meaning. The small prose of the Ukrainian modernist artist opens the way to comprehending the depths of the national worldview, marks the current space of human existence in the time of the Great Liberation War.